Simulation study on a three-evaporator air conditioning system for simultaneous indoor air temperature and humidity control. (1st December 2017) - Yan, Huaxia; Xia, Yudong; Deng, Shiming
Highlights: Two controllers for a TEAC system were developed. Controllability tests for the two controllers were carried out. Indoor RH could be indirectly controlled using the first capacity controller. Simultaneous temperature and RH control can be realized with the improved controller. Abstract: A multi-evaporator air conditioning (MEAC) system, which may also be called a multi-split air conditioning system or variable refrigerant flow system in the open literature, may be regarded as one of the energy conscious air conditioning applications. However, most MEAC systems currently focus on air temperature control only, so that the potential of using MEAC system in achieving energy saving has not yet been fully utilized. In this paper, based on the previous extensive related research on modeling and controlling both single evaporator air conditioning systems and MEAC systems, a capacity controller for a three-evaporator air conditioning (TEAC) system was developed. Results of simulative controllability tests for the capacity controller demonstrated that, indoor air temperature could be directly controlled using the capacity controller, but indoor relative humidity can be improved and maintained at acceptable levels. Based on the operating characteristics of the TEAC system, the capacity controller was further improved and thus an improved controller was developed. Two tests to verify the performances of the improved controller were conducted. The test results showed that simultaneous indoor air temperature and humidity control of a TEAC system could be achieved using the improved controller.